2017
DOI: 10.1016/j.cell.2017.09.051
|View full text |Cite
|
Sign up to set email alerts
|

The Human Knockout Gene CLYBL Connects Itaconate to Vitamin B12

Abstract: Summary CLYBL encodes a ubiquitously expressed mitochondrial enzyme, conserved across all vertebrates, whose cellular activity and pathway assignment are unknown. Its homozygous loss is tolerated in seemingly healthy individuals, with reduced circulating B12 levels being the only and consistent phenotype reported to date. Here, by combining enzymology, structural biology and activity-based metabolomics we report that CLYBL operates as a citramalyl-CoA lyase in mammalian cells. Cells lacking CLYBL accumulate ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 53 publications
6
111
1
Order By: Relevance
“…Itaconyl‐CoA is an intermediate of itaconate catabolism. It has been reported that itaconate inactivates vitamin B12 in the absence of CLYBL . Mechanistically, knockout of CLYBL promotes the accumulation of itaconyl‐CoA, which directly causes vitamin B12 degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Itaconyl‐CoA is an intermediate of itaconate catabolism. It has been reported that itaconate inactivates vitamin B12 in the absence of CLYBL . Mechanistically, knockout of CLYBL promotes the accumulation of itaconyl‐CoA, which directly causes vitamin B12 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that itaconate inactivates vitamin B12 in the absence of CLYBL. 18 Mechanistically, knockout of CLYBL promotes the accumulation of itaconyl-CoA, which directly causes vitamin B12 degradation. Severe deficiency of vitamin B12 is a common cause of anemia and neurological impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one cluster that includes metazoan sequences, that of the itaconate-detoxifying CLYBL. [25] The Rv2498c cluster is actinobacterial-specific and contains only uncharacterised sequences (seventy-two in UnitProt). A variety of enzymatic activities has been described for PF03328 members, but the majority fall into two classes as it is evident from the tree: aldehyde-lyases (EC:4.1.2) and oxo-acid-lyases (EC:4.1.3); Rv2498c belongs to the latter.…”
Section: Resultsmentioning
confidence: 99%
“…We showed for the first time that Mtb can dissimilate itaconate, a hallmark macrophage metabolite synthesised after lipopolysaccharide activation during host inflammatory response to fight infection and also linked to Vitamin B12 deficiency. [25, 35, 36]. Itaconate is present in some prokaryotes, but its exact physiological function remains unclear.…”
Section: Discussionmentioning
confidence: 99%